The Influence of Inflation on the Poverty Level in Medan City: A Case Study of Labor and Human Resources - Ahmad Fadlan; Rizal P. Lubis (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
Poverty is one of the problems faced by many developing countries, including Indonesia, where the poverty rate is high, or the population lives below the poverty line, and poverty creates obstacles to limited people's happiness in terms of food, clothing, and housing. As the province has a relatively dense population and few job opportunities, it is feared that this will increase poverty in the region. Therefore, we need a solution to overcome and reduce poverty in Medan. This study analyzes the impact of unemployment, education level, investment, inflation, population, and labor force on poverty in Medan City from 2008 to 2020. The data comes from the Central Bureau of Statistics for Medan City, on behalf of several publications in figures, poverty data, and Medan City Data in various editions for 2008-2020. This study uses the CFA (Confirmatory Factor Analysis) and multiple linear regression methods. The results of this study indicate that the variables of inflation and labor force have a significant effect on poverty in Medan City, while the variables of unemployment, education, investment, and population in Medan City have no significant effect on poverty in Medan City.Keywords: Human resources, inflation, labor, poverty